As dimensões pedagógica, didática, tecnológica e científica na formação e no desenvolvimento profissional dos professores no Brasil e em Portugal - Nascimento, Franc-Lane Sousa Carvalho do (2015)
In this study, entitled "The pedagogical, didactic, technological and scientific dimensions that training and professional development of teachers in Brazil and Portugal", we discuss in which perspective these courses are forming and contributing to the development of professional teaching, in order to experience those dimensions in a balanced way, aiming to qualify the pedagogical practice in the context of the 21th century. The center of this study is teachers’ initial formation. We have defined the following research problem: What are the perceptions, divergent and convergent factors among these initial training courses for teachers, and their contributions relating to professional development and construction of the pedagogical, didactic, technological and scientific dimensions in Brazil and Portugal? Our main objective is analyzing with comparative basis the initial training courses for teachers in Brazil and Portugal, considering professional development and the importance of pedagogical, didactic, technological and scientific dimensions. The theoretical and methodological procedures are guided by qualitative and quantitative research. As instruments and research techniques we have used field observation, questionnaires and semi-structured interviews. We have based ourselves on authors such as Freire (1996); Franco, Libâneo and Pimenta (20007); Garcia (1999); Ramalho, Nuñez and Gauthier (2004); Houssaye (2004); Pintassilgo and Oliveira (2013); Shulman (2005); Saviani (2008); Nóvoa (1997); among others. We have conducted a study according to comparative methodology, by using official documents, laws, decrees, opinions and specialized literature on teacher training. After analyzing those and followed by a reflection period, which provided better understanding of the two realities. Thus, the thesis we defend, is that the Pedagogical Education University Course in Brazil and the Professional Masters in Portugal, as teacher training models, must be based on knowledge about pedagogical, didactic, scientific and technological dimensions, as guiding references for educational practices of teachers engaged to Early Childhood Education and early years of Primary Education, promoting professional teaching development and qualitative improvements of basic education. The survey results showed differences and similarities between teacher training courses in Brazil and Portugal. Initial training in Portugal counts with predominance of pedagogical and scientific dimensions at the expense of didactic and technological ones, and teachers consider propitious curriculum restructuring to improve utilization of ICT. In Brazil, a greater relevance is given to pedagogical and didactic dimensions; disadvantaging the scientific and technological ones. Teachers and students specify the urge to improve the systematization of the curriculum in order to promote these four dimensions experience. Therefore, for the two realities studied, the four dimensions are not being applied in a balanced way, making it difficult to guide a formation that can promote teachers’ professional development in the future. However, in the past years, we have experienced the expansion of functions and action fields, the improvement regarding the disciplines offer, the increasing hours of activities and the reformulation of the study programs. We suggest that the UEMA and ESELx, rethink current initial training, overcome the gap between theory and practice and restructure the study programs by updating pedagogical, didactic, scientific and technological dimensions, which are fundamental to form teachers that are teaching and educating in 21th century schools.